The Vitality of Matter: a Wax in the Work of Jadwiga Maziarska, Read from the Perspective of Posthumanism - Smolińska, Marta (Sensus Historiae, 2020)
Jadwiga Maziarska is widely recognized as the precursor of matter painting in Poland. The issue, however, becomes more interesting when it is pointed out that in the repertoire, the material frequently used by the artist was wax - an organic substance associated with vitality, emotionality, sensuality, fluidity and tactility. Maziarska began her romance with wax around 1955, using it with pleasure and obtaining intensely haptic effects. The material is a significant, active visual component of a work of art and cannot be separated from the representation. In the context of posthumanism, wax – as a bee production used in art for centuries – seems to be particularly interesting, and the way in which Maziarska used it gives it a special vitality and puts it at its “complicity” in creating the final effect of the work. The text puts forward a provocative thesis that the theory of material started by Rudolf Arnheim in the 1920s would do well without posthumanism.